Ligustilide Ameliorates Memory Deficiency in APP/PS1 Transgenic Mice via Restoring Mitochondrial Dysfunction. (10th July 2018) - Xu, Yi-Jun; Mei, Yu; Qu, Zi-Ling; Zhang, Shi-Jie; Zhao, Wei; Fang, Jian-Song; Wu, Jun; Yang, Cong; Liu, Si-Jun; Fang, Yong-Qi; Wang, Qi; Zhang, Yong-Bin
Abstract : Ligustilide, the main lipophilic component of Radix angelicae sinensis, has been shown to ameliorate cognitive dysfunction in a few Alzheimer's disease mouse models, but its mechanism is not fully understood. In this study, we employed 7-month-old APP/PS1 mice to explore whether LIG is able to protect against Alzheimer's disease progression. The Morris water maze and Y-maze test results showed that eight weeks of intragastric administration of LIG (10 mg/kg, 40 mg/kg) every day improved memory deficit in APP/PS1 mice. The thioflavin-S staining and Western blot results (A β 1 - 42 monomer/oligomer, APP, ADAM10, SAPP α, and PreP) showed that LIG reduced A β levels in the brain of APP/PS1 mice. Transmission electron microscopy analysis showed that LIG reduced the mitochondria number and increased the mitochondrial length in the hippocampal CA1 area of APP/PS1 mice. A reduced level of Drp1 (fission) and increased levels of Mfn1, Mfn2, and Opa1 (fusion) were found in APP/PS1 mice treated with LIG. An increased ATP level in the brain and increased activities of cytochrome c oxidase (CCO) and succinate dehydrogenase (SDH) in mitochondrion separated from the hippocampus and cortex revealed that LIG alleviated mitochondrial dysfunction. LIG exerts an antioxidation effect via reducing the levels of malondialdehyde (MDA) and reactive oxygen species (ROS) and increasing the activity of Mn-SOD in the brain. Elevated levels of PSD-95, synaptophysin, and synapsin 1 in both the hippocampus and cortex indicated that LIG provided synaptic protection. These findings show that treatment with LIG ameliorates mitochondrial dynamics and morphology issues, improves mitochondrial function, reduces A β levels in the brain, restores the synaptic structure, and ameliorates memory deficit in APP/PS1 mice. These results imply that LIG may serve as a potential antidementia drug.